The Role and Potential of Money Waqf Through Baitul Mal wa Tamwil in Efforts to Alleviate Poverty Based on Pondok Pesantren - Achmad Dzikri Rajuli; Iltizam Umma Aqelia Hayatunnufus; Ahmad Azzam Nouvaldi (Proceeding of International Conference on Islamic Boarding School, 2025)
The research conducted focuses on discussing how the role and potential of cash waqf collected by Baitul Mal Wa Tamwil (syariah cooperative), after the cash waqf funds have been collected, are managed by the sharia cooperative for efforts to alleviate poverty based on Islamic boarding schools. The method used in this research is literature study (Library Research) towards books and reading materials related to the discussion. The research results show the role and potential of cash waqf for Islamic boarding school-based poverty alleviation. It shows that sharia cooperatives that are present in Islamic boarding school-based educational institutions can be the spearhead in collecting cash waqf because to carry out cash waqf you don't need to wait to be rich or established, anyone can carry out cash waqf with a small nominal amount such as five thousand rupiah, so that with the collected cash waqf capital, you can immediately use it according to the purpose, such as making investments by providing convenience in terms of financing to the community around the boarding school. Islamic boarding school with small profit sharing so as not to burden the customers. Apart from that, sharia cooperatives, apart from providing financing, have another very important role in supervising customers, namely by empowering, spiritual and physical development with religious knowledge and sharia-based family financial planning as well as providing business assistance so that the objectives of the financing can be achieved in accordance with the plans that have been prepared.